Rapid and sensitive real-time recombinase polymerase amplification for detection of Marek's disease virus. (December 2019) - Zeng, Fanwen; Wu, Miaoli; Ma, Lei; Han, Zongxi; Shi, Yue; Zhang, Yanping; Liu, Changjun; Zhang, Shouquan; Cong, Feng; Liu, Shengwang
Abstract: Marek's disease (MD) is one of the most devastating diseases of poultry. It's caused by the highly infectious alphaherpesvirus MD virus serotype 1 (MDV-1). In this study, a rapid and easy-to-use assay based on recombinase polymerase amplification (RPA) was developed for MDV detection. Primer-probe sets targeting the highly conserved region of Meq gene were designed and applied to the RPA assay. The assay was carried out on a real-time thermostatic fluorescence detector at 39 °C for 20 min. As revealed by the results, no cross-reactions were found with the Newcastle disease virus (NDV), chicken infectious anemia virus (CAV), infectious bursal disease virus (IBDV), avian infectious bronchitis virus (IBV), infectious laryngotracheitis virus (ILTV), avain influenza virus (AIV), avian leucosis virus (ALV), avian reovirus (ARV), Marek's disease virus serotype 2 (MDV-2) and turkey herpes virus (HVT), indicating appropriate specificity of the assay. Plasmid DNA standards were used to determine the sensitivity of the assay and the detection limit was 10 2 copies/μL. To further evaluate the clinical performance, 94 clinical samples were subjected to the RPA assay and 28 samples were tested MDV positive, suggesting that the real-time RPA assay was sufficient enough for clinical sample detection. Thus, a highly specific and sensitive real-time RPA assay was established and validated as a candidate for MDV diagnosis. Additionally, the portability of real-time RPA assay makes it suitable to be potentially applied in clinical diagnosis in the field, especially in resource-limited settings. Highlights: A real-time RPA assay was developed and evaluated for rapid detection of MDV. The real-time RPA assay was highly specific and sensitive. The real-time RPA assay was an alternative to PCR methods. The real-time RPA assay had the potential of use in field.